Cardiac Stem Cells for Myocardial Regeneration: They Are Not Alone - Yin, Yee Leong; Wai, Hoe Ng; Ellison-Hughes, Georgina M.; Jun, Jie Tan (Frontiers Media, 2017)
Heart failure is the number one killer worldwide with ~50% of patients dying within 5 years of prognosis. The discovery of stem cells, which are capable of repairing the damaged portion of the heart, has created a field of cardiac regenerative medicine, which explores various types of stem cells, either autologous or endogenous, in the hope of finding the “holy grail” stem cell candidate to slow down and reverse the disease progression. However, there are many challenges that need to be overcome in the search of such a cell candidate. The ideal cells have to survive the harsh infarcted environment, retain their phenotype upon administration, and engraft and be activated to initiate repair and regeneration in vivo. Early bench and bedside experiments mostly focused on bone marrow-derived cells; however, heart regeneration requires multiple coordinations and interactions between various cell types and the extracellular matrix to form new cardiomyocytes and vasculature. There is an observed trend that when more than one cell is coadministered and cotransplanted into infarcted animal models the degree of regeneration is enhanced, when compared to single-cell administration. This review focuses on stem cell candidates, which have also been tested in human trials, and summarizes findings that explore the interactions between various stem cells in heart regenerative therapy.